A reference to altar paintings in the Kotor archives of the 15th and the beginning of the 16th centuries: Madonna di Misericordia and Immaculata Concepitone - Živković Valentina (Zograf, 2004)
New iconographies themes, but also well-developed and enriched older program solutions, are the most vivid expression of the theological teachings and piety of an epoch. Some of the favorite themes in European art at that time were the Madonna di Misericordia and the Immaculata Conceptione. Written sources lead us to conclude that these iconographies solutions existed and were developed in the Kotor area. The Madonna di Misericordia was made for members of a religious brotherhood, while the Immaculata Conceptione is mentioned in reference to a chapel of the same name, in the church of the monastery of the Franciscan Observants of St. Bernardin. Like the demand for the wider accessibility of theological books intended for layman (breviaries and Psalters), so the increasing demand for altar paintings reflected new trends in the Catholic Church that developed from the 13th century according to the decisions of the 4th Lateran Council. The most important role in developing the new aspect of piety in towns was played by the members of the Franciscan and Dominican orders. Besides the many novelties they introduced in religious practice, they also gave a strong impetus to the veneration of holy pictures and to the development of new iconographies solutions. Altar paintings were frequently commissioned by the brotherhoods who reflected the spiritual and commercial life of the town through their religious activities and craftsmanship. It was for the brotherhood of St. Trifun that the painting of Our Lady of Mercy was produced, the existence of which is indirectly recorded by means of a decree of the brotherhood written in 1413. On the other hand, an even more exhaustive amount of information, both about this and about the Altar of the Immaculate Conception in the Franciscan church, is found in the wills of the Kotor inhabitants. On their deathbeds, the testators frequently bequeathed especially revered paintings or donations to have them produced, as acts of charity and as bequests. The information in the wills testifies to the fact that, at the very beginning of the 16th century, a chapel of the Immaculate Conception existed in Kotor that housed a much venerated painting of the Immaculata Conceptione, a theme especially supported by the Franciscans in their debates in medieval times. The possibility that a developed iconographies form of the Immaculata Conceptione existed is confirmed by the icon of Our Lady of Škrpjel, created about half a century prior to any mention of the painting in the Franciscan chapel, whose iconography already contained the elements of the Immaculata Conceptione.